Seven-day dietary nitrate supplementation clinically significantly improves basal macrovascular function in postmenopausal women: a randomized, placebo-controlled, double-blind, crossover clinical trial - Delgado Spicuzza, Jocelyn M.; Gosalia, Jigar; Zhong, Liezhou; Bondonno, Catherine; Petersen, Kristina S.; De Souza, Mary Jane; Alipour, Elmira; Kim-Shapiro, Daniel B.; Somani, Yasina B.; Proctor, David N. (Frontiers in Nutrition, 2024)
Introduction: Cardiovascular disease (CVD) is the leading cause of death in women, with increased risk following menopause. Dietary intake of beetroot juice and other plant-based nitrate-rich foods is a promising non-pharmacological strategy for increasing systemic nitric oxide and improving endothelial function in elderly populations. The purpose of this randomized, placebo-controlled, double blind, crossover clinical trial was to determine the effects of short-term dietary nitrate (NO3 -) supplementation, in the form of beetroot juice, on resting macrovascular endothelial function and endothelial resistance to whole-arm ischemia-reperfusion (IR) injury in postmenopausal women at two distinct stages of menopause. Methods: Early-(1-6 years following their final menstrual period (FMP), n=12) and late-(6+ years FMP, n=12) postmenopausal women consumed nitrate-rich (400 mg NO3 -/70mL) and nitrate-depleted beetroot juice (approximately 40 mg NO3 -/70 mL, placebo) daily for 7 days. Brachial artery flow-mediated dilation (FMD) was measured pre-supplementation (Day 0), and approximately 24 hours after the last beetroot juice (BR) dose (Day 8, post-7-day BR). Following, FMD was measured immediately post-IR injury and 15-minutes later (recovery). Results: Results of the linear mixed effects model revealed a significantly greater increase in resting FMD with 7-days of BRnitrate compared to BRplacebo (mean difference of 2.21%, 95 % CI [0.082, 4.34], p=0.042), however, neither treatment blunted the decline in post-IR injury FMD in either postmenopausal group. Our results suggest that 7-day BRnitrate-mediated endothelial protection is lost within the 24-hr. period following the final dose of BRnitrate. Conclusion: Our findings demonstrate that nitrate-mediated postmenopausal endothelial protection is dependent on the chronobiological variations in dietary nitrate metabolism and the timing of supplementation in relation to IR injury.